Revisiting the Role of Astrocytic MAOB in Parkinson's Disease - Nam, Min-Ho; Sa, Moonsun; Ju, Yeon Ha; Park, Mingu Gordon; Lee, C. Justin (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Monoamine oxidase-B (MAOB) has been believed to mediate the degradation of monoamine neurotransmitters such as dopamine. However, this traditional belief has been challenged by demonstrating that it is not MAOB but MAOA which mediates dopamine degradation. Instead, MAOB mediates the aberrant synthesis of GABA and hydrogen peroxide (H2O2) in reactive astrocytes of Parkinson's disease (PD). Astrocytic GABA tonically suppresses the dopaminergic neuronal activity, whereas H2O2 aggravates astrocytic reactivity and dopaminergic neuronal death. Recently discovered reversible MAOB inhibitors reduce reactive astrogliosis and restore dopaminergic neuronal activity to alleviate PD symptoms in rodents. In this perspective, we redefine the role of MAOB for the aberrant suppression and deterioration of dopaminergic neurons through excessive GABA and H2O2 synthesis of reactive astrocytes in PD.